GAMBARAN JUMLAH CD4 PADA PASIEN HIV/AIDS DI KLINIK VCT RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI -DESEMBER 2013 - Rini Aptriani; Fridayenti "; Alex Barus (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
HIV / AIDS is caused by infection with Human Immunodeficiency Virus. This virus infects a cell that has a molecular Cluster of Differentiation 4 (CD4). Counting the number of CD4 is a way to assess the immunity of patients with HIV / AIDS. The purpose of this research was to know describe of CD4 count in HIV / AIDS in Clinic VCT Arifin Achmad General Hospital of Riau Province during January to December 2013. This was a descriptive retrospective study. Data is used about 88 medical records of HIV / AIDS patients. Data obtained from this study is the highest frequency of HIV / AIDS was found at the age of 30-39 years (42.04%) and male gender (63.64%). Based on the type of job most are self-employed (52.27%). Based on the risk factors most infections come from clients (45.46%). Based on clinical stage, stage I (10.23%), stage II (34.09%), stage III (45.45%), and stage IV (10.23%). CD4 cell counts of HIV / AIDS patients <200 cells/mm3 (72.73%), CD4 cell count 200-499 cells/mm3 (25%), and CD4 cell count ≥ 500 cells/mm3 (2.27%).Keywords: HIV/AIDS, CD4 count